Brown Rice Inhibits Development of Nonalcoholic Fatty Liver Disease in Obese Zucker (fa/fa) Rats by Increasing Lipid Oxidation Via Activation of Retinoic Acid Synthesis. Issue 9 (5th July 2021) - Matsumoto, Yu; Fujita, Saya; Yamagishi, Ayano; Shirai, Tomomi; Maeda, Yukie; Suzuki, Tsukasa; Kobayashi, Ken-ichi; Inoue, Jun; Yamamoto, Yuji
ABSTRACT: Background: White rice and its unrefined form, brown rice, contain numerous compounds that are beneficial to human health. However, the starch content of rice can contribute to obesity, a main risk factor for nonalcoholic fatty liver disease (NAFLD). Objectives: We investigated the effect of rice consumption on NAFLD and its underlying molecular mechanism. Methods: We randomly divided 7-week-old male obese Zucker ( fa / fa ) rats, an animal model of NAFLD, into 3 groups ( n = 10 each) fed 1 of 3 diets for 10 weeks: a control diet (Cont; AIN-93G diet; 53% cornstarch), a white rice diet (WR; AIN-93G diet with cornstarch replaced with white rice powder), or a brown rice diet (BR; AIN-93G diet with cornstarch replaced with brown rice powder). Liver fat accumulation and gene expression related to lipid and vitamin A metabolisms, including retinoic acid (RA) signaling, were analyzed. Results: Hepatic lipid values were significantly decreased in the BR group compared with the Cont group, by 0.4-fold ( P < 0.05). The expression of genes related to hepatic fatty acid oxidation, such as carnitine palmitoyltransferase 2, was approximately 2.1-fold higher in the BR group than the Cont group ( P < 0.05). The expression of peroxisomal acyl-coenzyme A oxidase 1 and acyl-CoA dehydrogenase medium chain was also significantly increased, by 1.6-fold, in the BR group compared with the Cont group ( P < 0.05). The expression of VLDL-secretion-related genes, such as microsomal triglyceride transfer protein, was also significantly higher in the BR group (2.4-fold; P < 0.05). Furthermore, aldehyde dehydrogenase 1 family member A1, an RA synthase gene, was 2-fold higher in the BR group than the Cont group ( P < 0.05). Conclusions: Brown rice prevented development of NAFLD in obese Zucker ( fa / fa ) rats. The beneficial effects of pregelatinized rice on NAFLD could be manifested as increased fatty acid oxidation and VLDL secretion, which are regulated by RA signaling.